Airway autoantibodies are determinants of asthma severity. Issue 6 (1st December 2022) - Salter, Brittany; Zhao, Nan; Son, Kiho; Tan, Nadia Suray; Dvorkin-Gheva, Anna; Radford, Katherine; LaVigne, Nicola; Huang, Chynna; Kjarsgaard, Melanie; Li, Quan-Zhen; Tselios, Konstantinos; Lim, Hui Fang; et al.
Background: Local airway autoimmune responses may contribute to steroid dependence and persistent eosinophilia in severe asthma. Auto-IgG antibodies directed against granule proteins such as eosinophil peroxidase (EPX), macrophage scavenger receptor with collagenous structure (MARCO) and nuclear/extranuclear antigens (antinuclear antibodies (ANAs)) have been reported. Our objective was to describe the prevalence and clinical characteristics of asthmatic patients with airway autoreactivity, and to assess if this could be predicted from clinical history of autoreactivity. Methods: We analysed anti-EPX, anti-MARCO and ANAs in 218 sputum samples collected prospectively from 148 asthmatic patients, and evaluated their association with lung function parameters, blood/airway inflammation, severity indices and exacerbations. Additionally, 107 of these patients consented to fill out an autoimmune checklist to determine personal/family history of systemic autoimmune disease and symptoms. Results: Out of the 148 patients, 59 (40%) were anti-EPX IgG +, 53 (36%) were anti-MARCO IgG + and 64 out of 129 (50%) had ≥2 nuclear/extranuclear autoreactivities. A composite airway autoreactivity score (CAAS) demonstrated that 82 patients (55%) had ≥2 airway autoreactivities (considered as CAAS + ). Increased airway eosinophil degranulation (OR 15.1, 95% CI 1.1–199.4), increased blood leukocytes (OR 3.5, 95% CI 1.3–10.1) and reduced blood lymphocytes (OR 0.19, 95% CI 0.04–0.84) predicted CAAS + . A third of CAAS + patients reported an exacerbation, associated with increased anti-EPX and/or anti-MARCO IgG (p<0.05). While no association was found between family history or personal diagnosis of autoimmune disease, 30% of CAAS + asthmatic patients reported sicca symptoms (p=0.02). Current anti-inflammatory (inhaled/oral corticosteroids and/or adjunct anti-interleukin-5 biologics) treatment does not attenuate airway autoantibodies, irrespective of eosinophil suppression. Conclusion: We report 55% of moderate–severe asthmatic patients to have airway autoreactivity that persists despite anti-inflammatory treatment and is associated with exacerbations. Moderate–severe asthmatics have autoreactivities to eosinophil granule proteins, macrophage scavenger receptors and nuclear antigens. These patients have airway eosinophilia, peripheral lymphopenia, increased sputum lymphocytes and recurrent infections. https://bit.ly/3xwHfvf